2020
DOI: 10.1101/2020.12.04.412072
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying the interplay between rapid bacterial evolution within the mouse intestine and transmission between hosts

Abstract: SummaryDue to limitations on high-resolution strain tracking, selection dynamics during gut-microbiota colonization and transmission between hosts remain mostly mysterious. Here, we introduced hundreds of barcoded Escherichia coli strains into germ-free mice and quantified strain-level dynamics and metagenomic changes. Mutants involved in motility and utilization of abundant metabolites were reproducibly selected within days. Even with rapid selection, coprophagy enforced similar barcode distributions across c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…If causative mutants existed in the inoculum prior to infection (e.g., in the colony that was picked to generate the barcoded strain), we would expect the same set of barcodes to expand; however, different sets of barcodes expanded across all three experimental barcoded libraries (e.g., abscess clones in Figure 4 are different). If we assume a fixed mutation rate, then we would expect a similar number of clones to expand across animals, as observed in Jasinska et al, 2020 and in Vasquez et al, 2020 ; however, we observe a bimodal distribution of either 0 expanded clones or ~5–100 expanded clones. Furthermore, since liver abscesses are relatively small and discrete but consist of multiple clones, causative mutations would have had to arise in different bacterial cells that were also clustered together in physical space, which seems extremely unlikely.…”
Section: Discussionmentioning
confidence: 53%
“…If causative mutants existed in the inoculum prior to infection (e.g., in the colony that was picked to generate the barcoded strain), we would expect the same set of barcodes to expand; however, different sets of barcodes expanded across all three experimental barcoded libraries (e.g., abscess clones in Figure 4 are different). If we assume a fixed mutation rate, then we would expect a similar number of clones to expand across animals, as observed in Jasinska et al, 2020 and in Vasquez et al, 2020 ; however, we observe a bimodal distribution of either 0 expanded clones or ~5–100 expanded clones. Furthermore, since liver abscesses are relatively small and discrete but consist of multiple clones, causative mutations would have had to arise in different bacterial cells that were also clustered together in physical space, which seems extremely unlikely.…”
Section: Discussionmentioning
confidence: 53%
“…Future experiments could test these predictions quantitatively using genetic barcoding techniques ( 74 76 ), both in animal models ( 12 ) and potentially even in humans ( 77 ). For example, by introducing libraries of barcoded strains and tracking their relative fluctuations in later fecal samples, it should be possible to directly measure the effective rate of genetic drift in Eq.…”
Section: Discussionmentioning
confidence: 99%
“…These high rates of cell turnover create enormous opportunities for rapid evolutionary change: the trillions of bacteria within a single human colon produce more than a billion new mutations every day ( 7 ), and tens of thousands of bacterial generations will typically elapse within a single human lifetime ( 1 , 8 ). Consistent with these estimates, a growing number of empirical studies, ranging from experimental evolution in mouse models ( 9 12 ) to longitudinal sequencing of human subjects ( 7 , 13 20 ), have shown that genetic variants can sweep through resident populations of gut bacteria on timescales of weeks and months. The causes and consequences of this genetic turnover could play an important role in mediating the stability and resilience of this diverse microbial ecosystem ( 21 ).…”
mentioning
confidence: 80%
“…As an extreme example, studies of how bacteria adapt to survive high levels of an antibiotic must be carefully designed to avoid selecting for mutations that enhance adhesion to the walls of a test tube [ 20 ]. Organs-on-chips [ 21 ] and mice with humanized microbiota [ 22 ], while powerful, do not mimic in vivo conditions well enough to avoid system-dependent selective pressures [ 23 ]. By contrast, rigorous genomic signatures of in-host adaptation can conclusively indicate the presence of selection [ 8 , 19 ].…”
Section: Introductionmentioning
confidence: 99%